Consumer Acceptance for Vegetable Pigeonpea through front line Demonstrations in Central Gujarat - A. K. Rai , S. Khajuria , Kanak Lata , J. K. Jadav , Rajkumar; B. S. Khadda (Indian Journal of Extension Education, 2017)
Conventional pigeonpea (Cajanus cajan (L.) Millsp.) is harvested as seed but for the purpose of vegetable, it is harvested as pods when it is immature. At two stages it is a nutritious and delicious vegetable and forms a substitute for green pea (Pisum sativum (L.). Pigeonpea is one of the most important pulse crops of the Panchmahals district of Gujarat. However, productivity of pigeonpea in the district is very low. Attempts are made to improve productivity and to increase area under pigeonpea by adopting HYVs (High Yielding Variety). In order to compare and contrast conventional pigeonpea with HYVs varieties, 75 frontline demonstrations were carried out in a systematic manner on farmers’ field to show the worth of new varieties in comparison to local check and thereby convincing farmers about potentialities of improved production management practices of pigeonpea for further adoption, involving feasible and effective scientific package of practices. The demonstrations clearly showed enhancement of productivity, at the same time area under pigeonpea cultivation was also noticed to be enhanced. The yield (green pod) was found to increase from 4300 kg/ha in local check to 7300 kg/ha in demonstrations. Similarly, the benefit cost ratio for HYVs varieties was found to increase to 3.22 as compared to local check (2.27). The economics and benefit cost ratio can be further improved to 3.23 by giving slightly higher inputs for cultivation and marketing. The impact of FLDs was analyzed which showed improvement of knowledge and satisfaction of farmers as the main reason for mass scale adoption.